2020
DOI: 10.3389/fphys.2020.00891
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-6: A Friend or Foe of Pregnancy and Parturition? Evidence From Functional Studies in Fetal Membrane Cells

Abstract: Objective: Protection of the fetus within the amniotic sac is primarily attained by remodeling fetal membrane (amniochorion) cells through cyclic epithelial to mesenchymal and mesenchymal to epithelial (EMT and MET) transitions. Endocrine and paracrine factors regulate EMT and MET during pregnancy. At term, increased oxidative stress forces a terminal state of EMT and inflammation, predisposing to membrane weakening and rupture. IL-6 is a constitutively expressed cytokine during gestation, but it is elevated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 66 publications
(119 reference statements)
2
18
0
Order By: Relevance
“…In rhesus monkeys, for instance, IL-1β stimulates IL-17 production from chorioamniotic T-cells, propagating the inflammatory response in these layers [ 61 ]. On the other hand, IL-6, on its own, does not induce any inflammatory and cellular transition changes in AECs [ 117 ]. However, IL-6 stimulates the production of PGE2 with a concomitant decrease in PGDH in AECs, increasing prostaglandins within the fetal membranes especially with a continuous influx of IL-6 from other feto-maternal units [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…In rhesus monkeys, for instance, IL-1β stimulates IL-17 production from chorioamniotic T-cells, propagating the inflammatory response in these layers [ 61 ]. On the other hand, IL-6, on its own, does not induce any inflammatory and cellular transition changes in AECs [ 117 ]. However, IL-6 stimulates the production of PGE2 with a concomitant decrease in PGDH in AECs, increasing prostaglandins within the fetal membranes especially with a continuous influx of IL-6 from other feto-maternal units [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…54 This finding indirectly supports a prior report by Richardson et al that amnion mesenchymal cells are transitioned epithelial cells and not necessarily permanent constituents. 55,56,54 They are seen in the extracellular matrix during their transient state to become epithelial cells again. 14 During this state of cyclic transition, cells do not express markers that are expressed by primary cells (i.e., amnion epithelial cells) and do not perform similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports indicate that the plasma of preeclamptic patients contains elevated levels of IL-6, a multifunctional cytokine that regulates, among other things, the acute phase reaction and modulates both pro- and anti-inflammatory events, and may play roles in the pathogenesis of preeclampsia by serving as a source of a key circulating factor that promotes systemic maternal endothelial cell dysfunction [ 55 ]. Additionally, while many of the functions of IL-6 have not been explained yet, it is assumed that IL-6 is a good biomarker for adverse pregnancies [ 56 ]. In this study it was found that all tested compounds, i.e., methyldopa and all flavonoids, increased mRNA IL-6 expression, but every combined administration of a flavonoid together with methyldopa showed a strong contrary inhibitory effect when compared to the value for methyldopa in JEG-3 cells.…”
Section: Discussionmentioning
confidence: 99%